"Voluntarily Admitted Against My Will": Patient Perspectives on Effects of, and Alternatives to, Coercion in Psychiatric Care for Self-Injury. (December 2019) - Gerle, Ellen; Fischer, Anne; Lundh, Lars-Gunnar
Introduction: Various forms of coercion are used in the psychiatric care of patients with self-injurious behaviors, but there is little research on how these are perceived by the patients. The aim of this study was to investigate how 6 patients, who had received care for self-injurious behavior, perceived coercion and how they think coercion could be avoided. Methods: This study employed a qualitative design with 6 semistructured interviews and interpretative phenomenological analysis. Results: Three main themes were identified: keep voluntary care voluntary, apportioning control and responsibility, and dialogue and participation. Constant supervision was described as the most destructive form of coercion. To enable self-responsibility, a reduction of control and supervision was advocated. Calls were made for a treatment based on the assumption that there is a desire, on behalf of the patients, to get better. Conclusions: The use of coercion in the psychiatric care of patients with self-injurious behavior can be reduced by increasing predictability, by listening to the patient with genuine interest, and by involving the patient in decisions regarding their treatment.